Analytical nonlinear collisional dynamics of near-threshold eigenmodes. (27th February 2019) - Duarte, V.N.; Gorelenkov, N.N.
Abstract: The nonlinear dynamics of isolated, near-threshold waves is studied in the presence of strong resonant particle scattering. In this limit, a simple closed-form analytical solution is found and compared with numerical simulations, which shows reasonable agreement when the wave evolves quasi-steadily to saturation, even for moderate tokamak-relevant collisionality levels. The solution can be useful in verifying codes that deal with Alfvénic instabilities and thermal plasma turbulence in fusion plasmas, as well as a rapid means for predicting and analyzing experimental outcome.